Unraveling the Light‐Induced Degradation Mechanisms of CH 3 NH 3 PbI 3 Perovskite Films - Nickel, Norbert H.; Lang, Felix; Brus, Victor V.; Shargaieva, Oleksandra; Rappich, Jörg (Advanced electronic materials, 2017)
Organic–inorganic perovskite solar cells have experienced a remarkable development. In a short period of time power conversion efficiencies have jumped to values of more than 22%. However, the stability of these devices is an important subject. The stability of CH 3 NH 3 PbI 3 perovskite films is investigated using visible and ultraviolet light in oxygen atmosphere and in vacuum. Illumination in O 2 atmosphere results in a swift degradation. Oxygen acts as a catalyst decomposing methylammonium ions (CH 3 NH 3 + ) into CH 3 NH 2 and hydrogen. In vacuum, another degradation mechanism is observed. Prolonged illumination of the samples with photons from blue and UV light‐emitting diodes also results in dissociation of the methylammonium ion into CH 3 NH 2 and hydrogen. In both cases the resulting molecules are highly mobile at room temperature and diffuse out of the samples. The light‐induced dissociation of CH 3 NH 3 + is accompanied by the generation of localized defects in the band gap of the perovskite. Furthermore, the experimental data clearly show that the molecular orbitals of CH 3 NH 3 + are not in resonance with the energy bands of the perovskite lattice.